2018
DOI: 10.1097/md.0000000000009672
|View full text |Cite
|
Sign up to set email alerts
|

Anti epidermal growth factor receptor therapy in small bowel adenocarcinoma

Abstract: Rationale:Small bowel adenocarcinoma (SBA) is an uncommon gastrointestinal cancer, thus limited data about treatment for advanced disease are available. The lack of specific guidelines has justified the use of therapeutic protocols usually applied in advanced colorectal cancer. Few and preliminary data have suggested possible clinical benefit from the use of target therapy such as bevacizumab and cetuximab.Patient concerns:We present the case of a young woman who was admitted to the emergency department for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Tumor molecular analysis may provide the rationale for the use of targeted therapies. For instance, in several case reports of metastatic SBC, the presence of KRAS wild-type has been demonstrated to predict responsiveness to antiepidermal growth factor receptor monoclonal antibodies (cetuximab and panitumumab) alone or combined with chemotherapy [ 207 , 208 ]. In contrast, nine patients with metastatic SBC KRAS wild-type showed no response to panitumumab in a phase 2 clinical trial (7 showing progression and 2 showing stable disease) [ 209 ].…”
Section: Celiac Disease and Small Bowel Carcinomamentioning
confidence: 99%
“…Tumor molecular analysis may provide the rationale for the use of targeted therapies. For instance, in several case reports of metastatic SBC, the presence of KRAS wild-type has been demonstrated to predict responsiveness to antiepidermal growth factor receptor monoclonal antibodies (cetuximab and panitumumab) alone or combined with chemotherapy [ 207 , 208 ]. In contrast, nine patients with metastatic SBC KRAS wild-type showed no response to panitumumab in a phase 2 clinical trial (7 showing progression and 2 showing stable disease) [ 209 ].…”
Section: Celiac Disease and Small Bowel Carcinomamentioning
confidence: 99%
“…Several molecular alterations may suggest the response to novel therapies. In particular, KRAS wild-type mutational status has been demonstrated to predict responsiveness to anti-epidermal growth factor receptor monoclonal antibodies cetuximab and panitumumab alone or combined with chemotherapy in metastatic SBC in several case reports [76,77]. Conversely, a recent phase 2 clinical trial of panitumumab showed no response rate of this drug in nine patients with metastatic KRAS wild-type SBC, of which one was associated to inflammatory bowel disease and two to Lynch syndrome [78].…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…Several molecular alterations may suggest the response to novel therapies. In particular, KRAS wild-type mutational status has been demonstrated to predict responsiveness to anti-epidermal growth factor receptor monoclonal antibodies cetuximab and panitumumab alone or combined with chemotherapy in metastatic SBC in several case reports [75,77]. Conversely, a recent phase 2 clinical trial of panitumumab showed no response rate of this drug in nine patients with metastatic KRAS wild-type SBC, of which one was associated to inflammatory bowel disease and two to Lynch syndrome [78].…”
Section: Prognosis and Treatmentmentioning
confidence: 99%